Compressive Strength and Light Transmission of Translucent Concrete by Using Optical Fiber - Ambali, Dian Pranata Putra Pranata; Lolo, Jumiarti Andi; Handyaningtyas, Garudea Martha; Tasik, Gerson Kona; Goran, Heinprianto Kewegok (Politeknik Sukabumi, 2023)
Global warming or an increase in the earth's temperature triggers the innovation of green building materials to reduce the contribution of buildings to the effect of greenhouse gases. One of the building materials innovations in reducing energy use is translucent concrete. However, the addition of optical fiber as a material capable of transmitting light in a transparent concrete mixture can reduce the compressive strength of the concrete. This study aimed to determine the ability of translucent concrete to transmit light and how strong the compressive strength of translucent concrete using optical fiber. Measurement of light transmission gives the result that the larger the diameter of the optical fiber used, the greater the value of light transmission. While testing the compressive strength of concrete shows that the use of optical fiber in transparent concrete reduces the compressive strength of concrete by about 26%. The addition of silica fume in the translucent concrete mixture has an impact on increasing the compressive strength which is almost equivalent to normal concrete. Variations in the arrangement of optical fibers in the transparent concrete mixture were also carried out, namely straight and random arrangements, then the results obtained that translucent concrete with straight optical fiber arrangements had a better light transmission value than translucent concrete with random optical fiber arrangements. On the other hand, the compressive strength of translucent concrete with straight optical fiber arrangement is lower than that of translucent concrete with random optical fiber arrangement.